2015
DOI: 10.1097/phm.0000000000000240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treadmill Inclination on Hemiparetic Gait

Abstract: In subjects with hemiparesis, the addition of inclination is a stimulus capable of enhancing the effects of partial body weight-support treadmill gait training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
2
23
0
3
Order By: Relevance
“…Our results suggest that HISTT does not improve or worsen spatiotemporal symmetry and that walking speed can improve and be retained regardless of changes in symmetry. These findings do not appear to be related to the high-intensities involved in HISTT because other studies using a variety of moderate-intensity training interventions have also found improvements in walking speed with no change in symmetry (although direct relations were not tested) (36)(37)(38)(39)(40). Only a couple studies have reported the direct relation between change in walking speed and spatiotemporal symmetry; one found that increased propulsive asymmetry was associated with greater improvements in walking speed (39), while another (41) found no relation between changes in walking speed and changes in spatiotemporal symmetry.…”
Section: Discussionmentioning
confidence: 76%
“…Our results suggest that HISTT does not improve or worsen spatiotemporal symmetry and that walking speed can improve and be retained regardless of changes in symmetry. These findings do not appear to be related to the high-intensities involved in HISTT because other studies using a variety of moderate-intensity training interventions have also found improvements in walking speed with no change in symmetry (although direct relations were not tested) (36)(37)(38)(39)(40). Only a couple studies have reported the direct relation between change in walking speed and spatiotemporal symmetry; one found that increased propulsive asymmetry was associated with greater improvements in walking speed (39), while another (41) found no relation between changes in walking speed and changes in spatiotemporal symmetry.…”
Section: Discussionmentioning
confidence: 76%
“…We excluded studies that assessed only gait parameters, based on our selection criteria ( Figure 1 ). Four studies reported significantly improved lower limb recovery and balance following four weeks of 20–30-minute cycling or body weight supported treadmill training [ 42 , 43 , 45 , 46 ]. Likewise, eight weeks of moderate AE improved functional lower limb mobility after training while balance was significantly improved at follow-up 8 weeks later [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample size was calculated by using an online calculator [31], and the variable gait speed (in meters per second) was adopted as the primary outcome measure. According to a previous study involving individuals with post-stroke hemiparesis who performed treadmill training with partial weight support and anterior inclination of 10° (experimental) and no inclination (control) [26], standard deviations observed in the experimental and control groups were 0.1 and 0.2, respectively. The sample size was calculated from these data to detect a difference in gait speed between the groups of 0.18 m/s (α = 5% and power = 80%) since the minimum detectable difference in the gait speed for patients with chronic stroke was 0.18 m/s [32].…”
Section: Methodsmentioning
confidence: 99%
“…Treadmill training can be carried out according to several protocols and also associated with difficult factors such as anterior or posterior inclination of the treadmill, direction changes in movement (backward), and an increase in load in order to increase weight [2325]. Specifically, regarding the treadmill anterior inclination, some studies have been carried out in patients with stroke [20, 23, 2628] given that walking on inclined surfaces is an activity commonly faced by community-dwelling people with locomotor impairments [26]. All of these studies observed improvement in gait variables—such as increased walking speed and range of motion of lower limbs, longer paretic step length, and improved gait balance and symmetry—during or after training on an inclined treadmill.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation